Regulation of Intrinsic and Bystander T Follicular Helper Cell Differentiation and Autoimmunity by Tsc1 - Zhang, Shimeng; Li, Lei; Xie, Danli; Reddy, Srija; Sleasman, John W.; Ma, Li; Zhong, Xiao-Ping (Frontiers in Immunology, 2021)
T follicular helper (Tfh) cells promote germinal center (GC) B cell responses to develop effective humoral immunity against pathogens. However, dysregulated Tfh cells can also trigger autoantibody production and the development of autoimmune diseases. We report here that Tsc1, a regulator for mTOR signaling, plays differential roles in Tfh cell/GC B cell responses in the steady state and in immune responses to antigen immunization. In the steady state, Tsc1 in T cells intrinsically suppresses spontaneous GC-Tfh cell differentiation and subsequent GC-B cell formation and autoantibody production. In immune responses to antigen immunization, Tsc1 in T cells is required for efficient GC-Tfh cell expansion, GC-B cell induction, and antigen-specific antibody responses, at least in part via promoting GC-Tfh cell mitochondrial integrity and survival. Interestingly, in mixed bone marrow chimeric mice reconstituted with both wild-type and T cell-specific Tsc1-deficient bone marrow cells, Tsc1 deficiency leads to enhanced GC-Tfh cell differentiation of wild-type CD4 T cells and increased accumulation of wild-type T regulatory cells and T follicular regulatory cells. Such bystander GC-Tfh cell differentiation suggests a potential mechanism that could trigger self-reactive GC-Tfh cell/GC responses and autoimmunity via neighboring GC-Tfh cells.